Effects and quantification of acid runoff from sulfide-bearing rock deposited during construction of Highway E18, Norway. (November 2015) - Hindar, Atle; Nordstrom, D. Kirk
Highlights: We studied runoff from three deposits of sulfide-bearing rock. Sulfur release rates indicate 250–800 years of acid runoff. The concentrations of seven metals increased by a factor of 25–400. Al-hydroxysulfates dominated precipitates formed at the deposits. Active water treatment is needed to avoid harmful ecological effects. Abstract: The Highway E18 between the cities of Grimstad and Kristiansand, southern Norway, constructed in the period 2006–2009, cuts through sulfide-bearing rock. The geology of this area is dominated by slowly-weathering gneiss and granites, and oxidation of fresh rock surfaces can result in acidification of surface water. Sulfide-containing rock waste from excavations during construction work was therefore deposited in three waste rock deposits off-site. The deposits consist of 630, 000–2, 360, 000 metric tons of waste rock material. Shell sand and limestone gravel were added in layers in adequate amounts to mitigate initial acid runoff in one of the deposits. The shell sand addition was not adequate in the two others. The pH in the effluents from these two was reduced from 4.9–6.5 to 4.0–4.6, and Al concentrations increased from below 0.4 mg/L to 10–20 mg/L. Stream concentrations of trace metals increased by a factor of 25–400, highest for Ni, and then in decreasing order for Co, Mn, Cd, Zn and Cu. Concentrations of As, Cr and Fe remained unchanged. Ratios of Co/Ni and Cd/Zn indicate that the metal sources for these pair of metals are sphalerite and pyrite, respectively. Based on surveys and established critical limits for Al, surface waters downstream became toxic to fish and invertebrates. The sulfur release rates were remarkably stable in the monitoring period at all three sites. Annual sulfur release was 0.1–0.4% of the total amount of sulfur in the deposit, indicating release periods of 250–800 years. Precipitates of Al-hydroxysulfates, well-known from mining sites, were found at the base of the deposits, in streams and also along the ocean shore-line. The effects of added neutralization agents in the deposits and in treatment areas downstream gradually decreased, as indicated by reduced stream pH over time. Active measures are needed to avoid harmful ecological effects in the future.